Differentiated Instruction in Teaching English: A Case Study In Inclusive Classroom - Lovy Amalia (Language-Edu, 2019)
AbstractThe request of including Special education needs students in regular classroom increasing in Senior High School. The first inclusive school in Kediri makes the researcher interested in knowing about the teachers’ differentiated instruction used in teaching English for students in inclusive classroom, technique in teaching English and the environment support. Visually impairment and autism students were chosen. The study uses qualitative case-study. Observation and interview result show that the teacher focused on their characteristic to give differentiated instruction. Techniques were grammar- translation method and co-operative learning strategy. The environment has a good support and makes a good result.Key words: Inclusive Classroom, Differentiated Instruction, Teaching Strategy,  Environment Support ,Autism, Visually Impairment